POLA AFILIASI INFORMAL ORGANISASI GERAKAN MAHASISWA DENGAN PARTAI POLITIK (STUDI KASUS SISTEM KADERISASI KESATUAN AKSI MAHASISWA MUSLIM INDONESIA DENGAN PARTAI KEADILAN SEJAHTERA) - Linggar K Suseno; Budi Setyono; Supratiwi . (Journal of Politic and Government Studies, 2014)
A long controversy about an ideal relationship which is required to be knitted between instrument of political infrastructure, interest group and political party in a statehood framework, has always been an actual topic. The purpose of this study to describe the general relationship between students as a interest group against the movement patterns of political parties - the regeneration system - as one element of a political infrastructure, in an effort to create a healthy political climate. For some people who support the need of a harmonious wickerwork between the two of those institution, the existence of the affiliation is actively necessity. However, Not a few among the other observers, have different opinion to respond this social phenomena. Two of the leading persons who are standing against the indication of affiliate relation which is built between the two of those institution, Julien Benda and Arief Budiman. Benda, this well-known French man assumes that ‘interest’ becomes a differentiator key of fundamental framework between the two of those institutions. As well as Benda said, Arif who is well-known in student movement over the era of 1996 reveals things in common. For Arif, the moral movement which is carried by interest group, such as student movement organization is required to be given a space when it is joggled with political movement, which becomes the main characteristic of political parties. After the long controvercy is taken place, the appearance of Kesatuan Aksi Mahasiswa Muslim Indonesia (KAMMI) and Partai Keadilan Sejahtera (PKS) in the same time and era, reformation era was not occurred without intentional element. As an interest distributor tool of populace of tarbiyah, The appearance of the two of those institution which have different roles and functions, becomes a sign that there is new paradigm about the relationship between interest group and political party after the fall of new order regime. One of the form of affiliations which is knitted between the two of those institution of tarbiyah movement can be